UJI AKTIVITAS ANTIBAKTERI STAPHYLOCOCCUS AUREUS DAN SALMONELLA TYPHI DARI HASIL MIKROENKAPSULASI MINYAK ATSIRI ROGO (PREMNA SERRATIFOLIA LINN) - Nursin, Nursin; Nurliana, Laily; Imran, Imran; Musta, Rustam (IKIP Mataram, 2019)
Antibacterial activity test Staphylococcus aureus and Salmonella typhihas been performed by microencapsulation product of rogo essential oil (Premnaserratifolia Linn). This study aims to determine rogo oil activity test and microencapsulation results as antibacterial S. aureus and S. typhi. The results of antibacterial activity of rogo liquid oil to S. aureus and S. Typhi bacteria showed different inhibitory power of each concentration variation of 12.5%, 25%, 50% and 100% with 100% concentration as the best inhibitor for both bacteria. While the antibacterial activity test of S. aureus and S. typhi from microencapsulated rogo oil: maltodextrin showed the difference of each variation of concentration 1:10; 1:12; 1:14; 1:16 and 1:18 with a 1:14 composition of S. aureus and 1:18 in S. typhi as the best ratio of activity power. The antibacterial activity test between liquid rogo oil and microencapsulated result shows the difference, but it can be concluded that the inhibitory power of rogo oil from microencapsulation is more inhibited than 100% rogo oil.